Bladder outflow obstruction induced by ipratropium bromide. Issue 762 (April 1989) - Lozewicz, S.
Abstract : Three cases are described in which bladder outflow obstruction was produced by ipratropium bromide, a widely used anticholinergic bronchodilator which has been regarded as virtually free from systemic side effects. Many patients treated with ipratropium bromide are elderly males in whom prostatic hypertrophy is common and in these circumstances, large doses should be used with caution.